2013
DOI: 10.1371/journal.pone.0055776
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Activation in HIV/HCV Coinfection Correlates with Cognitive Impairment

Abstract: Coinfection with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) challenges the immune system with two viruses that elicit distinct immune responses. Chronic immune activation is a hallmark of HIV infection and an accurate indicator of disease progression. Suppressing HIV viremia by antiretroviral therapy (ART) effectively prolongs life and significantly improves immune function. HIV/HCV coinfected individuals have peripheral immune activation despite effective ART control of HIV viral load. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 50 publications
4
39
1
1
Order By: Relevance
“…Among the studies that measured the GDS Rempel et al, 2013;Sun et al, 2013), the meta-analysis revealed statistically significant differences between groups (SMD = 0.56, 95% CI: 0.36, 0.75, The co-infected group showed poorer visual memory and motor functioning than the HIV mono-infected group prior to antiretroviral therapy Before cART, a greater percentage of coinfected patients performed poorly on the neuropsychology summary score (HIV/HCV: 50%; HIV: 20%). After being exposed for six months to antiretroviral therapy, no differences were found between groups HIV/HCV > HIV before cART HIV/HCV ≅ HIV after cART Perry et al p < .00001).…”
Section: Meta-analysesmentioning
confidence: 98%
See 4 more Smart Citations
“…Among the studies that measured the GDS Rempel et al, 2013;Sun et al, 2013), the meta-analysis revealed statistically significant differences between groups (SMD = 0.56, 95% CI: 0.36, 0.75, The co-infected group showed poorer visual memory and motor functioning than the HIV mono-infected group prior to antiretroviral therapy Before cART, a greater percentage of coinfected patients performed poorly on the neuropsychology summary score (HIV/HCV: 50%; HIV: 20%). After being exposed for six months to antiretroviral therapy, no differences were found between groups HIV/HCV > HIV before cART HIV/HCV ≅ HIV after cART Perry et al p < .00001).…”
Section: Meta-analysesmentioning
confidence: 98%
“…Overall, most studies reported that the HIV/HCV co-infected patients were generally more impaired than HIV and HCV monoinfected patients and controls Ciccarelli et al, 2013;Clifford, Evans, Yang, & Gulick, 2005;Devlin et al, 2012;von Giesen et al, 2004;Hinkin et al, 2008;Letendre et al, 2005;Martin et al, 2004;Parsons et al, 2006;Rempel et al, 2013;Ryan, Morgello, Isaacs, Naseer, & Gerits, 2004;Sun et al, 2013;Vivithanaporn et al, 2012). Other studies found no differences on cognitive performance between HIV/ HCV and HIV mono-infected groups (Aronow, Weston, Pezeshki, & Lazarus, 2008;Thiyagarajan et al, 2010), between HIV/HCV and HCV mono-infected groups (Clifford et al, 2009;Perry et al, 2005), and between HIV/HCV and both HIV and HCV mono-infected groups (Thein et al, 2007).…”
Section: Cognitive Impairmentmentioning
confidence: 98%
See 3 more Smart Citations